Penerapan Asesmen Autentik dalam Praktikum IPA di Sekolah Dasar - Diana Rossa Martatiyana; Faisal Madani (Jurnal Elementaria Edukasia, 2023)
Authentic assessment is an evaluation method that actively involves students in the learning process and assesses their abilities in real conditions. In the context of science learning in elementary schools, authentic assessment can be applied through practice. Science practicum provides students with experience in understanding material concepts directly and also improves cognitive abilities in observing, reasoning and communication skills. The aim of this research is to find out how authentic assessment is used in science learning activities, especially in practice in elementary schools, so that it can provide an understanding of the application of authentic assessment which is very important in learning activities, one of which is to improve the quality of learning and improve students' abilities. This research uses a literature review method by analyzing and collecting data from scientific articles related to research topics and problems. The research results show that the application of authentic assessment can improve learning in science practicum activities and improve students' practical skills as well as provide an assessment of the process and results so that teachers can determine good treatment of students.